Effects of Dietary Mannan Oligosaccharides on Non-Specific Immunity, Intestinal Health, and Antibiotic Resistance Genes in Pacific White Shrimp Litopenaeus vannamei - Wang, Tiantian; Yang, Jinzhu; Lin, Gang; Li, Mingzhu; Zhu, Ronghua; Zhang, Yanjiao; Mai, Kangsen (Frontiers in Immunology, 2021)
Five isonitrogenous and isolipid diets were formulated by adding 0%, 0.02%, 0.04%, 0.08% and 0.16% mannan oligosaccharides product (hereinafter called MOS) in the basal diet. Each diet was randomly fed to one group with 4 replicates of shrimp (Litopenaeus vannamei) in an 8-week feeding trial. The results showed that dietary MOS improved the growth performance and the ability of digestion of shrimp. Dietary MOS significantly increased the activity of TSOD, CAT and GPX and decreased the content of MDA in plasma of shrimp. Dietary MOS significantly increased the activity of AKP and LZM in plasma and the hemocytes counts. Dietary MOS significantly up-regulated the expression of Toll, LZM, ALF, Crustin and HSP70 in hepatopancreas. And dietary MOS significantly up-regulated the expression of intestinal MUC-2, MUC-5B and MUC-19, while decreased the expression of intestinal MUC-1 and MIF. Dietary MOS improved the bacterial diversity, increased the abundance of Lactobacillus, Bifidobacterium, Blautia and Pseudoalteromonas and decreased the abundance of Vibrio in the intestine. Shrimp fed MOS diets showed lower mortality after challenged by Vibrio parahaemolyticus. Remarkably, ARGs and MGEs content were reduced by supplementation of MOS. The present results showed that diet with MOS supplementation enhanced the antioxidant capacity and immunity, improved intestinal immunity, optimized intestinal microecology, mitigate the degree of antibiotic resistance and increased the resistance to V. parahaemolyticus in L. vannamei, especially when supplemented at 0.08% and 0.16%.